Calcium and vitamin D supplementation and increased risk of serrated polyps: results from a randomised clinical trial. Issue 3 (1st March 2018) - Crockett, Seth D; Barry, Elizabeth L; Mott, Leila A; Ahnen, Dennis J; Robertson, Douglas J; Anderson, Joseph C; Wallace, Kristen; Burke, Carol A; Bresalier, Robert S; Figueiredo, Jane C; Snover, Dale C; Baron, John A
Abstract : Objective: Serrated lesions such as sessile serrated adenomas or polyps (SSA/Ps) are important colorectal cancer precursors, but aetiological factors for these lesions are largely unknown. We aimed to determine the effects of calcium and vitamin D supplementation on the incidence of serrated polyps (SPs) in general and hyperplastic polyps and SSA/Ps specifically. Design: Participants with one or more adenoma at baseline were randomised to receive 1200 mg/day of elemental calcium, 1000 IU/day of vitamin D3, both or neither agent. Treatment continued for 3 or 5 years, when risk of polyps was determined from surveillance colonoscopy (treatment phase). Outcomes after treatment ceased were also assessed (observational phase). Adjusted risk ratios (aRRs) of SPs were determined via multivariable generalised linear models. Results: SPs were diagnosed in 565 of 2058 (27.5%) participants during the treatment phase and 329/1108 (29.7%) during the observational phase. In total, 211 SSA/Ps were identified during follow-up. In the treatment phase, there was no effect of either calcium or vitamin D on incidence of SSA/Ps. However, during the later observational phase, we observed elevated risks of SSA/Ps associated with calcium alone and calcium+vitamin D treatment (aRR (95% CI): 2.65 (1.43 to 4.91) and 3.81 (1.25 to 11.64), respectively). Conclusion: In a large multicentre chemoprevention study, we found evidence that calcium and vitamin D supplementation increased the risk of SSA/Ps. This appeared to be a late effect: 6–10 years after supplementation began. These possible risks must be weighed against the benefits of calcium and vitamin D supplementation. Trial registration number: NCT00153816; Results.